Poor emotion regulation ability mediates the link between depressive symptoms and affective bipolarity. Issue 5 (4th July 2019) - Dejonckheere, Egon; Kalokerinos, Elise K.; Bastian, Brock; Kuppens, Peter
ABSTRACT: People's relationship between positive and negative affect varies on a continuum from relatively independent to bipolar opposites, with stronger bipolar opposition being termed affective bipolarity . Experiencing more depressive symptoms is associated with increased bipolarity, but the processes underlying this relation are not yet understood. Here, we sought to replicate this link, and to examine the role of two potential mediating mechanisms: emotion regulation ability, and trait brooding. Drawing from the Dynamic Model of Affect, we hypothesised that (a) a poor ability to regulate negative emotion, and (b) the tendency to brood over one's depressed feelings would predict stronger affective bipolarity, and mediate the relationship between depressive symptoms and affective bipolarity. To measure affective bipolarity, we calculated within-person affect correlations using two weeks of experience sampling data from a community sample ( n  = 100). Mediation analyses indicated that baseline assessments of an inability to regulate negative emotions in general, but not brooding specifically, mediated the relation between depressive symptoms and affective bipolarity. These findings highlight an initial mechanism through which depressive symptoms are associated with lower emotional complexity and flexibility.